The Role of Women Farmers Group on Agriculture Development in Jeruksawit Village - Ernoiz Antriyandarti; Alvina Damayanti; Annisa Setyaningrum; Atila Windi Kurniawati; Deandra Suci Nur; Dian Ayu Khairunnisa; Anggityas Werdining Pangesti; Desta Prasanthi Aggraini (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Agriculture development requires the role of many institutions. Achieving agricultural development is needed to develop economics. At the regional level, agriculture is one of the primary sources of livelihood. We need to solve problems in agriculture to achieve agricultural development. One institution that will be observed in this study is the women farmers group, their role in solving agricultural issues, and agriculture development strategy in the village. This study analyzes women farmers' role in agriculture development strategy in Jeruksawit Village, Gondangrejo, Karanganyar, Central Java. The primary research method used in this study is descriptive with an explanatory research approach. The location was chosen in Jeruksawit Village, Gondangrejo, Karanganyar, Central Java. The study was carried out from November to December 2021. The place was chosen because there is a women farmers group and some problems with agricultural developments. The data used are primary and secondary. The preliminary data were collected through in-depth interviews, field observation, and triangulation. To assess information for primary data, this study uses key informants as the information source. The secondary data were collected from Central Bureau Statistics Central Java, literature review, and farmers group archives. The analysis method used is the analysis of Miles and Huberman, which is carried out through data reduction, display of data collection, and verification. The results of this study show that the women farmers group plays an essential role in agriculture development by training farmers to increase farmers' education, doing comparative studies to understand agriculture better, providing partnerships between farmers, and providing agriculture counseling.